PELATIHAN PEMBUATAN POC BERBAHAN DASAR CANGKANG TELUR DAN DI INFLEMENTASIKAN KE TANAMAN PAK COY ( Brassica rapa L.) UNTUK MEWUJUDKAN PERTANIAN ORGANIK RAMAH LINGKUNGAN - Puja Afrida; Khairul Rizal; Yusmaidar Sepriani; Badrul Ainy Dalimunthe (Universitas Muhammadiyah Tapanuli Selatan, 2022)
This socialization and training was motivated by the manufacture of liquid organic fertilizer from eggshell waste, eggshell is a waste that is mostly produced by fast food traders, and they just throw it in the trash can even though the egg shells are not only for decoration or not for decoration. make full use of it even though egg shells contain nutrients that many plants need for fertilizer, increase public awareness that eggshell waste can be utilized. Liquid organic fertilizer We conduct training in the community or in farmer groups. This training aims to increase organic planting in the community. base with organic fertilizer